(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes the renaissance periods in the history of our country, their shortcomings, the role of constitutional reforms in the construction of the third renaissance, the stages of raising the legal consciousness of preschool children and providing them with basic knowledge.